2021
DOI: 10.33393/dti.2021.2192
|View full text |Cite
|
Sign up to set email alerts
|

Tamarind (Tamarindus indica L.) Seed a Candidate Protein Source with Potential for Combating SARS-CoV-2 Infection in Obesity

Abstract: Introduction: Obesity and coronavirus disease (COVID)-19 are overlapping pandemics, and one might worsen the other. Methods: This narrative review discusses one of the primary mechanisms to initiate acute respiratory distress syndrome, uncontrolled systemic inflammation in COVID-19, and presents a potential candidate for adjuvant treatment. Blocking the S protein binding to angiotensin-converting enzyme 2 (ACE-2) and the 3C-like protease (3CL pro) is an effective strategy against severe acute respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 82 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Studies have shown that the TTI acts on different mechanisms that involve the control of obesity and its associated effects, such as the production of hormones related to satiety, affecting the central nervous system and the small intestine; reduced food consumption and weight gain; improvement of the lipid profile; and reduction of the inflammatory process related to obesity, regardless of weight loss ( Lima et al, 2019 ). Thus, considering that TTI is a promising molecule concerning the mechanisms associated with the inhibition of ACE-2 ( Morais et al, 2021 ), was chosen to use the enzymes pepsin, trypsin, and chymotrypsin in this study to obtain the peptides from the theoretical TTIp (TTIp 56/287) by enzymatic hydrolysis in silico .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the TTI acts on different mechanisms that involve the control of obesity and its associated effects, such as the production of hormones related to satiety, affecting the central nervous system and the small intestine; reduced food consumption and weight gain; improvement of the lipid profile; and reduction of the inflammatory process related to obesity, regardless of weight loss ( Lima et al, 2019 ). Thus, considering that TTI is a promising molecule concerning the mechanisms associated with the inhibition of ACE-2 ( Morais et al, 2021 ), was chosen to use the enzymes pepsin, trypsin, and chymotrypsin in this study to obtain the peptides from the theoretical TTIp (TTIp 56/287) by enzymatic hydrolysis in silico .…”
Section: Discussionmentioning
confidence: 99%
“…Among the natural products, protease inhibitors are widely studied, especially trypsin inhibitors, extracted from seeds, purified, characterized, and evaluated for diverse functionalities and bioactivities ( Morais et al, 2021 ). Some examples are trypsin inhibitors that inhibit other serine proteases, such as chymotrypsin and human neutrophil elastase ( Ascenzi et al, 2003 , Lima et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are also ongoing studies that use phytochemicals, like bromhexine and phyto-flavonoid luteolin, which are validated to block the S-protein cleavage activation and membrane fusion [46] (Table 2). Another potential candidate for adjuvant treatment is the trypsin inhibitor tamarind, which in addition to several beneficial effects on the reduction of inflammatory markers, could inhibit alone or in combination with other drugs the action of proteases that facilitate the SARS-CoV-2 infection [47]. Cyclo-oxygenase-2 non-steroidal anti-inflammatory drugs Prevent inflammatory cytokine storm [67] TMPRSS2: transmembrane serine protease 2; ADAM17: a disintegrin and metalloprotease 17; NRP-1: neuropilin-1; CD147: cluster of differentiation 147; GRP78: glucose-regulated protein 78.…”
Section: Furin Primingmentioning
confidence: 99%
“…A review article of different plant parts, extraction solvents, and seed oil of Coriandrum sativum (Apiaceae) experimentally demonstrated anti-inflammatory effects in macrophages, mice, and rats ( Sari, Bellatasie & Ifora, 2021 ). A trypsin inhibitor protein from seed of Tamarindus indica (Fabaceae) is proposed to have utility for inhibiting proteases related to SAR-CoV-2 infection in the worsened inflammatory condition in obesity ( de Morais et al, 2021 ). Curcumin from Curcuma longa (Zingiberaceae) is also proposed as a potential prophylactic therapeutic for COVID-19 due to its observed antiviral activity against ten types of enveloped viruses that cause human diseases combined with an immunomodulatory effect ( Thimmulappa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%